Prevalence of anti-hepatitis C virus antibodies among blood donors and risky groups in Diyala - Hassan, Abdul-Razak S. (Journal of the Faculty of Medicine Baghdad, 2009)
Objective: To determine the prevalence of hepatitis C virus (HCV) infection among blood donors and risky population in Diyala province. Materials and methods: In this retrospective study, the records of HCV screening and confirmatory tests were reviewed for the period 1996-2001.Third generation Enzyme-linked immunosorbant assay (ELISA) and Enzyme immunoblot assay were used as screening and confirmatory tests respectively. Results: The prevalence of HCV infection among blood donors was 0.15%, with the highest in 1997. The highest prevalence rates were found among multiple blood recipient; hemophilia, thalassemia and hemodialysis patients (27.3%, 16.9% & 14.3%) respectively. Whereas, the patients with chronic hepatitis B infection and those with acute icteric hepatitis showed slightly elevated prevalence (2.9% & 2.1%) respectively. The overall prevalence in the province was 9.9/105 population. The mean age of infected patients was 29.7 years and the male: female ratio was 3:1. Conclusion: The prevalence of HCV infection in Diyala population is relatively low. However, the HCV infection is concentrated in certain risky groups, particularly multiple blood recipients.